Indirect Taxes: A Balance of Reources and Expenditure - Mundan, Aarti (Journal of Commerce and Trade, 2017)
India has federal system of Government and the division of taxes among the Centre and State Governments is very complex. Though, the Indian constitution creates a dual polity based on divided Governmental powers and functions, this division is not watertight compartment. Exact correspondence between resources and functions at different levels of the Government is not possible to secure in any federal system. The emergence of imbalances between functional responsibilities and financial resources is a characteristic feature of all federations. GST is also an information Technology driven tax mechanism. It clearly, shows a upward change in government revenue. It is further expected to have a charge on unlawful tax-aviodance. GST will benefit both governments as well as the consumers. Further, after the implementation of GST, the business will have to get GST ready software's. Hence, it is clear here that just registration is not enough for entire business management, government is planning a portal for easy excess monitoring. Here, it is notable that the increase in revenue which is being expected by the Government is not targeted from consumer’s pocket but from the tax-aviodance. The present paper gives a comparison and benefits between previous VAT and present GST. Classification-JEL: H 21, H 22, H 26, H 27.